Advanced tomographic methods in materials research and engineering - Banhart, John, 1958- (Oxford : Oxford University Press, 2008)
Tomography provides 3D images of materials or engineering components and an unprecedented insight into their internal structure. This book discusses developments in the field, such as the extension of tomographic methods to materials research and engineering.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Materials -- Research; Tomography -- Industrial applications; Nondestructive testing